2018
DOI: 10.1016/j.commatsci.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

On the transfer of cascades from primary damage codes to rate equation cluster dynamics and its relation to experiments

Abstract: Transferring displacement cascades from primary damage codes to rate equation cluster dynamics (RECD) is not straightforward, due to the inability of RECD to treat spatial correlations explicitly. A method, called ''sphere homogenization kinetic Monte Carlo" (SHKMC), has been proposed to produce a effective source term from a cascade database. This paper reviews the method and a few applications. SHKMC is based on a modified kinetic Monte Carlo algorithm to keep track of the homogenization process of defects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Under thermal aging, CD reproduces well AKMC results provided it is carefully parametrized with the same atomistic data [2,3] and that potential corrections are added to the classical formalism to handle concentrated alloys [7,8]. For materials under irradiation, it has been shown that provided input parameters in CD and OKMC are consistent, cluster size distributions are very similar for low volume fractions, even if distributions obtained with OKMC can be slightly broader than those obtained with CD [9]. Tests at higher volume fractions have not been performed, to our knowledge.…”
Section: Introductionmentioning
confidence: 72%
“…Under thermal aging, CD reproduces well AKMC results provided it is carefully parametrized with the same atomistic data [2,3] and that potential corrections are added to the classical formalism to handle concentrated alloys [7,8]. For materials under irradiation, it has been shown that provided input parameters in CD and OKMC are consistent, cluster size distributions are very similar for low volume fractions, even if distributions obtained with OKMC can be slightly broader than those obtained with CD [9]. Tests at higher volume fractions have not been performed, to our knowledge.…”
Section: Introductionmentioning
confidence: 72%
“…These models are thus capable of providing relevant information that closer to real materials. However, these simulations require that a large number of parameters (and the way they evolve with temperature) be known accurately, not to mention the impact of surfaces (Aliaga et al 2016) (Duan et al 2018) or the source term, as recently shown in (Jourdan and Crocombette 2018). This means that considerable effort must go into choosing the level of details to enter in the models to minimally perturb the results.…”
Section: Coupling With Other Methodsmentioning
confidence: 99%
“…In some very specific cases, it is possible to neglect some of the point defect reactions thus speeding up the calculations as was shown by (Pelaz et al 2007) in ion implanted Si, but in general one must account explicitly for both point defect populations. Furthermore, the very recent study by Jourdan et al (Jourdan and Crocombette 2018) shows that the cascade annealing depends on the point defect concentrations and must thus be evaluated on-the-fly or for different point defect concentrations unlike it has been typically done. The main outcome of all these studies is to point out as in the previous section that it is necessary to have a better understanding of how the point defect and point defect clusters mobilities are affected by solutes, temperatures and other point defects.…”
Section: Iv-1 Annealing Of Cascades and Source Term Determinationmentioning
confidence: 99%
“…The relaxation and evolution of the damage produced by cascade events occurs at comparatively long timescales, often comparable with the interval of time between the subsequent cascade events, especially in the low dose rate limit. The models that are being explored here span the interval from stochastic kMC approaches [35] to diffusion-mediated dislocation based models [36] to rate theory cluster dynamics type simulations that are expected to be able to help explain the observed evolution of radiation induced microstructures [37].…”
Section: Irradiation and Irradiation Modellingmentioning
confidence: 99%